The Influence of Learning Moral Creeds on Student Behavior at the Bustanul Ulum Guppi Private Madrasah Tsanawiyah, Tebing Tinggi City - Rajali, Tengku; Siregar, Abdul Rosip (STAI Tebing Tinggi Deli, 2023)
This research approach is a quantitative approach, namely research where the data obtained is related to numbers which causes the use of statistical analysis techniques. The results of the research in this thesis, based on the results of the analysis it is known that the rcount or rxy value is 0.868 much greater than rtable (which is 0.235 and 0.306). Because rxy is greater than rtable, thus the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, because there is a significant positive relationship between the effect of learning aqidah morals on student behavior at Madrasah Tsanawiyah Private Bustanul Ulum Guppi Tebing Tinggi City. Aqidah Akhlak Learning on student behavior at the Private Madrasah Tsanawiyah Bustanul Ulum Guppi Tebing Tinggi City. The analysis of this study has a high positive correlation, namely 0.868. This is in accordance with the results of observations in the field that teaching aqeedah akhlaq is taught by educators very well because in addition to containing all the material it also provides understanding to students, so they can understand and practice about aqeedah akhlaq learning. From these calculations it is obtained that the Coefficient of Determination is 75.3%. Thus it can be seen that the contribution of the influence of learning aqidah morals on student behavior in Madrasah Tsanawiyah Private Bustanul Ulum Guppi City of Tebing Tinggi is 75.3%.